DEVELOPING INNOVATION IN VIETNAM - Hoang Lan Chi; Hoang Xuan Long (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Innovation is attracting attention worldwide and in Vietnam. To develop innovation in Vietnam, it is necessary to analyze the domestic demand, determine the innovational relationship between businesses and the national innovation system, identify the orientations of innovation and the central tasks that need to be focused on and establish measures to promote state innovation. These are also issues that need to be discussed to better understand innovation in Vietnam. Code: 23050401